2017
DOI: 10.1007/s13730-017-0253-6
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment by tocilizumab without steroid in a very severe case of TAFRO syndrome

Abstract: A 59-year-old Japanese man was admitted to our hospital with leg edema, fatigue and fever. He had a past medical history of duodenal ulcer, fatty liver, hyperuricemia and positive rheumatoid factor, but was not receiving any medication. His son had died 2 years prior to this admission after following a clinical course that suggested TAFRO syndrome.The patient showed mild fever (about 37-38 °C), polypnea and severe leg edema on admission. Chest examination revealed decreased breath sounds in the right lung. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…Both iMCD‐TAFRO patients were anti‐IL‐6 nonresponders and all three iMCD‐NOS patients treated with anti‐IL‐6‐therapy responded. Importantly, there have been reports of iMCD‐TAFRO cases that have responded to anti‐IL‐6‐therapy and others that have not . The proteomic differences between the two groups may represent differences between clinical subtypes or be a signature of anti‐IL‐6 response.…”
Section: Discussionmentioning
confidence: 99%
“…Both iMCD‐TAFRO patients were anti‐IL‐6 nonresponders and all three iMCD‐NOS patients treated with anti‐IL‐6‐therapy responded. Importantly, there have been reports of iMCD‐TAFRO cases that have responded to anti‐IL‐6‐therapy and others that have not . The proteomic differences between the two groups may represent differences between clinical subtypes or be a signature of anti‐IL‐6 response.…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies have been reported to cause immune-mediated platelet transfusion-refractoriness [19]. In fact, several cases of TAFRO syndrome have been reported to present with refractoriness to platelet transfusions [5, 15, 16, 20, 21], suggesting that thrombocytopenia might occur as a result of antibody-mediated platelet destruction. A detailed analysis of the mechanism of antibody production against platelets could provide a key to understanding the pathogenesis of TAFRO syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Tocilizumab (TCZ) could be used safely in patients with renal impairment, and it might be a reasonable choice considering that excessive IL-6 secretion is one of the main pathophysiological events in TAFRO syndrome. Fujiki et al reported a case of TAFRO syndrome complicated with severe infection during corticosteroid therapy, which was successfully treated with TCZ alone [17]. However, cases of TCZ-resistant TAFRO syndrome have been reported [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Some severe cases might require temporary hemodialysis (HD). We reviewed previously reported cases of TAFRO syndrome requiring HD during the clinical course in the English literature and identified 19 cases (16 Japanese cases [17,19,20,28,33,[43][44][45][46][47][48][49][50][51]] and 3 non-Japanese cases [42,52,53]). Japanese patients were older than non-Japanese patients (mean age, 57.6 vs. 35.7 years).…”
Section: Discussionmentioning
confidence: 99%